2019
DOI: 10.18552/2019/idscmt5078
|View full text |Cite
|
Sign up to set email alerts
|

Use of recycled concrete aggregates in structural concrete

Abstract: The investigation herein focuses on studying the possibility of using recycled concrete aggregates in structural concrete. The study aims in investigating the uniaxial compressive, tensile and flexural strength of recycled aggregate concrete and behaviour of reinforced RAC beams by assessing several important aspects which may influence its behaviour. These aspects include the replacement percentage of recycled aggregates used in concrete and water to cement ratio. Concrete made with recycled concrete aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 6 publications
0
8
2
Order By: Relevance
“…Similar studies [16,33] have reported a reduction of 37% and 43% in compressive strength at 28 days for 100% replacement level, which is relatively higher than the results achieved in this study. Other studies [34,35] have reported a decrease of 25% at a 100% replacement level, which is lower than the present study. Hence, these research results are pretty satisfactory compared with the previous research studies of similar nature and scenarios.…”
Section: Discussioncontrasting
confidence: 97%
“…Similar studies [16,33] have reported a reduction of 37% and 43% in compressive strength at 28 days for 100% replacement level, which is relatively higher than the results achieved in this study. Other studies [34,35] have reported a decrease of 25% at a 100% replacement level, which is lower than the present study. Hence, these research results are pretty satisfactory compared with the previous research studies of similar nature and scenarios.…”
Section: Discussioncontrasting
confidence: 97%
“…Another alternative is to replace NA with different byproducts (Gupta et al, 2020), such as slag (Roslan et al, 2020) and construction and demolition waste (Gonzalez-Corominas et al, 2017). The application of either strategy curtails waste generation in a consumer society where it is problematic (Khan et al, 2019), such as the 865 Mt of construction and demolition waste generated in Europe alone on an annual basis (Eurostat, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recycled Concrete Aggregate (RCA) is a by-product from the demolition of aging concrete structures (Khan et al, 2019). However, the crushing of rejected concrete elements mainly from the precast concrete industry yields the highest quality RCA (Fiol et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the effect of replacing natural aggregates (NA) with recycled aggregates (RA) in HPC has been studied in detail [16,17]. It has been found that the simultaneous addition of coarse and fine RA reduced the mechanical properties of HPC [18], although to a lesser extent than in conventional vibrated concrete because of its denser microstructure [19]. Thus, while reductions of 40% of the mechanical properties of conventional concrete can be obtained when adding 100% coarse RA [20], those reductions for HPC have been found to be from 15% to 20%, for full replacement of coarse NA with RA [14].…”
Section: Introductionmentioning
confidence: 99%